Computing and validating trunk transverse surface area equations to assess swimmer’s drag force - Barbosa, Tiago M. (2018)
A couple of methods to assess drag force (i.e., computer fluid dynamics and velocity perturba5on method) need to include in the data input the trunk transverse surface area (TTSA). TTSA is measured with a planimeter, on screen measure area soPware of plane 2D digital images or body scan.